Chronotherapy with Cinacalcet has a striking effect on inhibition of parathyroid gland proliferation in rats with secondary hyperparathyroidism - Søren Egstrand; Maria Lerche Mace; Marya Morevati; Lars Henning Engelholm; Jesper Skovhus Thomsen; Annemarie Brüel; Klaus Olgaard; Ewa Lewin (PLoS ONE, 2025)
Secondary hyperparathyroidism (sHPT) is a significant clinical complication of CKD leading to bone abnormalities and cardiovascular disease. Current treatment based on activating the parathyroid calcium-sensing receptor (CaSR) using calcimimetics such as Cinacalcet, aims to decrease plasma PTH levels and inhibit the progression of parathyroid hyperplasia. In the present study, we found significant diurnal rhythmicity of Casr, encoding the Cinacalcet drug target in hyperplastic parathyroid glands (p = 0.006). In rats with sHPT, Cinacalcet treatment timed prior to the acrophase of Casr expression (chronotherapy: Cina1) was compared with the usual timing of treatment early in the active phase (conventional: Cina2). Without Cinacalcet treatment, induction of sHPT resulted in a significant increase in parathyroid proliferation in terms of Ki-67+ cells compared to that of control rats (p = 0.001). Conventional Cinacalcet treatment (Cina2) did not significantly reduce Ki-67 index compared to untreated rats with sHPT (p = 0.09). In contrast, chronotherapy treatment (Cina1) resulted in a marked inhibition of parathyroid proliferation by Ki-67+ cells compared to untreated rats with sHPT (p = 0.0001). We found significantly reduced parathyroid Ki-67 index using chronotherapy compared to conventional timing of Cinacalcet (Cina1 vs. Cina2: 0.92±0.14% vs. 2.46±0.37%, p = 0.006). Transcriptomic analysis showed that the reduced proliferation of Cina1 was associated with downregulation of genes involved in mitotic activity, together with an increased adaptive response of energy metabolism, as evident from upregulated pathways of Oxidative phosphorylation and TCA cycle compared to the untreated uremic group. Conclusively, it is shown that the inhibitory effect of Cinacalcet on parathyroid cell proliferation is markedly impacted by the timing of administration, suggesting a possible benefit of using chronotherapy in Cinacalcet treatment of sHPT.